2012
DOI: 10.1039/c2dt11913g
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic gold compounds: synthesis, biological characterization and investigation of their inhibition properties of the zinc finger protein PARP-1

Abstract: The new gold(III) complexes: [Au{2-(2'-pyridyl)imidazolate}Cl(2)] and [Au{2,6-bis(2'-benzimidazolate)pyridine}(OCOCH(3))] and the mono- and binuclear gold(I) complexes: [Au{2-(2'-pyridyl)imidazole}(PPh(3))](PF(6)), [Au(2-phenylimidazolate)(DAPTA)] (DAPTA = 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane), [(PPh(3)Au)(2)(2-R-imidazolate)](PF(6)) (R = 2-C(5)H(4)N, Ph) have been synthesized and characterized. The structure of the [(PPh(3)Au)(2){2-(2'-pyridyl)imidazolate)](PF(6)) complex was also character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…18,19 Information on the reactivity of the gold complexes with the PARP-1 zinc-finger domain was also obtained by high-resolution mass spectrometry, and an excellent correlation between PARP-1 inhibition in protein extracts and the ability of the complexes to bind to the zinc finger motif (in competition with zinc) was established. 18 Thus, in order to further investigate the mechanisms of action of the new heteronuclear complexes, we tested the mononuclear compounds 5 and 6 for their PARP-1 inhibition properties in vitro as reported in the Experimental section. The obtained preliminary results showed that the trinuclear Au-Fe compound 5 is a potent PARP-1 inhibitor with an IC 50 = 1± 0.5 μM, while the trinuclear Pd-Fe analogue 6 is much less effective with an IC 50 = 17± 0.8 μM.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Information on the reactivity of the gold complexes with the PARP-1 zinc-finger domain was also obtained by high-resolution mass spectrometry, and an excellent correlation between PARP-1 inhibition in protein extracts and the ability of the complexes to bind to the zinc finger motif (in competition with zinc) was established. 18 Thus, in order to further investigate the mechanisms of action of the new heteronuclear complexes, we tested the mononuclear compounds 5 and 6 for their PARP-1 inhibition properties in vitro as reported in the Experimental section. The obtained preliminary results showed that the trinuclear Au-Fe compound 5 is a potent PARP-1 inhibitor with an IC 50 = 1± 0.5 μM, while the trinuclear Pd-Fe analogue 6 is much less effective with an IC 50 = 17± 0.8 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in recent years several gold(III) compounds have shown promising anticancer effects related to the inhibition of different protein targets, such as the proteasome and specific zinc finger proteins [57], [58], [59], [60]. In this context, we cannot exclude that inhibition of AQP3 might influence the biological effects of the compounds towards cancer cells, although other studies need to be performed to validate such a hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Since the beginning of 21th century, a series of new gold(III) complexes turned out to be stable under physiological conditions and also exhibited appreciable in vitro and in vivo anticancer activity [12, 13, 1518]. Parish et al [19] described the synthesis of stable gold(III) complex using damp (2-(Dimethylamino)methyl)phenyl) as uni-negative bidentate ligand as an analogy in the structural features of cisplatin as neutral coordination complex in the mid of 1990s.…”
Section: Introductionmentioning
confidence: 99%